Intermolecular covalent interactions: a quantitative molecular orbital perspective - Santos, Lucas de Azevedo (2021)
This thesis reports detailed quantum chemical investigations on the nature and strength of intermolecular interactions in DmZ•••A– complexes, mediated via atoms Z of groups 15–17 in the periodic table, based on quantitative Kohn-Sham molecular orbital theory. In the first stage, accurate ab initio benchmark and density functional theory (DFT) validation studies have been done. For each type of bond, pnictogen bond (PnB) and chalcogen bond (ChB), and, for comparison, halogen bond (XB) and hydrogen bonds (HB), accurate trends in bond length and strength are computed, based on a consistent set of data from our validated relativistic DFT approach. The main purpose is to provide a unified picture of chalcogen bonds and pnictogen bonds, together with hydrogen bonds and halogen bonds. The analyses herein reveal that the intramolecular interactions have a strong covalent component and are certainly not dominantly electrostatic in nature, as it is incorrectly suggested by the s-hole model whose weaknesses are consistently exposed. The findings in this thesis work thus suggest that the commonly accepted designation "Non-Covalent Interactions (NCI)" for the pertinent intermolecular interactions does not properly cover their nature and it is proposed to replace this designation with the more appropriate "Intermolecular Covalent Interactions (ICI)".